The Moslem women between west and Islam - عباس عبد الستار عبد القادر (College of Education for Women, 2019)
The Moslem women between west and Islam ,This study deals with Muslim women from the west Pont of view in the oriental studies or the western media and how it was exposed to ill-treatment or evil-eyed by the west due to misunderstanding or it was done on purpose that they didn't comprehend how the women deals with Islam ,so this western view assured that Islam had disparaged the women's position and hindered her freedom, aiming at stabbing Islam and dislocate the Islamic tissue which is formed from man and women. This study has established with evidences the distance of this western view from reality Islam in fact raised and lifted women's position while the western women was living on the margin of life, robbed from most of her rights for long centuries. This study also deals with this matter through three axes, the first axis is related with the oriental studies, the second axis is related with western media, the third one is found in Islam, it focuses on the problem of numerical or numerous wives, and on the injustice rights between man . Finally, this study reached to appoint that Islam, is one of the most religions of the word has freedom and liberty in the matter of women. It is the only play ground through which women can established her being and personality without causing any harm to her dignity,honour and humanty,On what is really happening to western women, who has been robbed from her rights on account of equality or being equal with the other sex>